An Investigation into Project-Based Learning in Higher Education: The Case of EFL in Moroccan Universities - EL MOUDDEN, Amine; LAMKHANTER , Fouzia (International Journal of Language and Literary Studies, 2024)
Project-based learning has gained immense popularity as an innovative method that reinforces learners’ critical thinking, autonomous learning and collaboration. It is basically founded on constructivism and experiential theories wherein students learn by doing. The objective of using this method is to enable learners to construct knowledge through meaningful learning experiences using real-life themes. It is an expedition of discovery where learners are often required to choose, prepare and present a project about a given course-related topic. This study aimed to reveal Moroccan English majoring students’ perceptions towards the implementation of the Project-Based Method in learning English as a Foreign Language. 1857 B.A. students from various colleges of Arts and humanities were involved in responding to a questionnaire to collect quantitative and qualitative data. The descriptive statistics, after analysis, showed that project work develops several language and life skills, especially oral communication, vocabulary and creative-critical thinking. It also found out that using projects plays a focal role in enhancing learners’ sense of responsibility and confidence, motivation, and autonomous learning and provides a positive learning environment. However, the participants mentioned a variety of challenges to implementing projects at the university level, namely stage anxiety, scarcity of relevant information, and time constraints. Overall, the findings of the study suggest several pedagogical implications to better integrate project work at the university level taking advantage of the positive attitudes learners hold towards this learning approach.